Galaxy ASIST: A web-based platform for mapping and assessment of global standards of antimicrobial susceptibility: A case study in Acinetobacter baumannii genomes - Sharma, Tina; Kumar, Rakesh; Kalra, Jasmeer Singh; Singh, Shreya; Bhalla, Gurpreet Singh; Bhardwaj, Anshu (Frontiers in Microbiology, 2023)
Antimicrobial susceptibility testing (AST) is used to determine the susceptibility of an organism to antibiotics. Determination of susceptibility is based on MIC breakpoints and are provided by EUCAST and CLSI. Likewise, phenotypic classification criteria developed by CDC/ECDC is used for classification of pathogens into susceptible, multidrug resistant, extremely drug resistant or totally drug resistant categories. Whole genome sequencing (WGS) based diagnosis is now supplementing existing gold standard microbiology methods for rapid and more precise AST and therefore EUCAST recommended quality criteria to assess whole genome sequence for reporting the same. In this study, these three global standards, MIC breakpoints, phenotypic classification and genome quality, are applied to the largest publicly available data for Acinetobacter baumannii (AB), the most critical priority pathogen identified by WHO. An automated pipeline, Galaxy-ASIST, is designed and developed for characterization of clinical isolates based on these standards. Evaluation of over 6500 AB strains using Galaxy-ASIST indicated that only 10% of the publicly available datasets have metadata to implement these standards. Also, given that CLSI and EUCAST have different MIC breakpoints, discrepancies are observed in classification of resistant and susceptible isolates among these standards. It is therefore imperative that platforms are developed that allow evaluation of ever increasing phenotypic and genome sequence datasets for AST. Towards this, Galaxy-ASIST offers a centralized repository and a structured metadata architecture to provide a single globally acceptable framework for AST profiling of the clinical isolates based on global standards. The platform also offers subsequent fine mapping of antimicrobial resistant determinants. Galaxy-ASIST is freely available at https://ab-openlab.csir.res.in/asist.